Comments on "A fuzzy multi criteria approach for measuring sustainability performance of a supplier based on triple bottom line approach". (20th January 2021) - Mukherjee, Sayan
Abstract: This article contains comments on the paper published by Govindan et al. (2013) where the authors devised a method for measuring the sustainability performance of suppliers. Economic, environmental and social factors considered important for triple-bottom-line are used to rank and select the suppliers. Fuzzy TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) is used as a methodology to evaluate and select suppliers by capturing the subjective preference of the experts. This article proposes corrections to some of the equations used in Govindan et al. (2013). Highlights: A note on a previously published article. Identification of errors in Govindan et al. (2013). Corrections in equations denoting operations of fuzzy numbers.